Mitochondrial genome assembly and phylogenetic analysis of Upeneus japonicus (Houttuyn, 1782) from the East China Sea - Li Wang; Shouqiang Wang; Ye Lin; Shenghao Liu; Panjiao Liang; Linlin Zhao (Mitochondrial DNA. Part B. Resources, 2022)
The mitochondrial genome of Upeneus japonicus was successfully assembled by high-throughput sequencing data in this study. This is the first report on the complete mitochondrial genome of U. japonicus, with a total length of 16,535 bp, including 13 protein-coding genes (PCGs), two ribosomal RNA genes (rRNAs), 22 transfer RNA genes (tRNAs), and a control region (D-loop). The overall base composition is 26.05% A, 26.10% T, 29.14% C, and 18.71% G. Phylogenetic analysis showed that U. japonicus was grouped with its sister species U. tragula. The mitochondrial complete genome study of U. japonicus would lay the foundation for further studies in population genetics and evolutionary analysis.